1981
DOI: 10.1172/jci110069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibrinogenolytic products D and E on fibrinogen and albumin synthesis in the rat.

Abstract: A B S T R A C T Previous studies are in conflict over the effect of infusing mixed fibrinogen-fibrin degradation products on fibrinogen synthesis, as determined by changes in fibrinogen concentration or by incorporation of labeled amino acids into fibrinogen. We have injected purified homologous fragments D1 and E into rats and measured their fibrinogen and albumin synthetic rates by the [14C]carbonate technique, a method that provides quantitative estimates of hepatic secretory protein synthesis. Fibrinogen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1982
1982
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…It has been suggested that the plasminolytic fragments of fibrinogen, specifically fragment D, only stimulated an increased synthesis of fibrinogen because no increase in either haptoglobin or albumin was detected after infusion of fragment D into rabbits (6) and rats (5). Our data demonstrate that fragment D or E has no direct effect on the hepatocyte's production offibrinogen-rather that the stimulation comes through the action of fragment D or E or the leukocyte.…”
Section: Resultsmentioning
confidence: 55%
“…It has been suggested that the plasminolytic fragments of fibrinogen, specifically fragment D, only stimulated an increased synthesis of fibrinogen because no increase in either haptoglobin or albumin was detected after infusion of fragment D into rabbits (6) and rats (5). Our data demonstrate that fragment D or E has no direct effect on the hepatocyte's production offibrinogen-rather that the stimulation comes through the action of fragment D or E or the leukocyte.…”
Section: Resultsmentioning
confidence: 55%
“…For this particular molecule, the occurrence of a pseudo-cyclic form, stabilized by an intramolecular hydrogen bond, has been speculated (3). Such a conformation would meet the spatial dequirements postulated (3,4) for the ring dimension (5.15 A) to fit into the hydrophobic portion of the cellulose macromolecule. Moreover, detailed crystallographic investigations on MMNO (6)(7)(8) coupled with computer simulation (9) have underlined that the solvent molecule should possess an hydrophobic end, in order to prevent any segmental recombination of the cellulose chains.…”
Section: Introductionmentioning
confidence: 87%
“…In the search for new cellulose organic solvents, tertiary amine oxide molecules have particularly attracted attention (1)(2)(3)(4)(5). In the patents, a claim for tertiary amine oxide to be a solvent is to be cyclic, as for example N-methylmorpholine N-oxide (abbreviated MMNO).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, stimulation of fibrinogen synthesis by FDP fragment D (FDP-D) was 3-to 5-fold higher than by FDP fragment E (FDP-E) (4). A similar effect of FDP-D was subsequently seen in rats (5,6). In vitro perfusion of isolated rat liver (7) has also identified FDP-D ability to stimulate fibrinogen synthesis.…”
mentioning
confidence: 89%